Significance of Oxidative Stress Level Changing in Rat Cerebral Tissue following Hypobaric Hypoxia Exposure to Extreme/High Altitude and Different Exposure of Times - Muhammad Shoaib Tahir, Maged Almezgagi, Yu Zhang, Du Zhonglei, Adnan Bashir, Muhammad Ali, Wei Zhang, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To elucidate brain damage under hypobaric hypoxia and changes in oxidative stress with ac. exposure to hypoxia in rats. Study Design: Experimental study. Place and duration of study: Department of Basic Medicine, Medical College of Qinghai University, Qinghai Xining from 1st October 2020 to 15th March 2021. Methodology: Twenty four Sprague Dawley rats were randomly divided into 4 groups; control, 24hr, 48hr, and 72hr. Hypoxia was simulated at the altitude of 7000m in an automated hypobaric hypoxia simulator. In the control and hypoxia treatment groups, the blood sample and brain tissue samples were collected. For the biochemical estimation, activities of CAT, GPx, SOD and content of MDA were evaluated. Results: A significant reduces in the activities of catalase, glutathione peroxidase and superoxide dismutase was observed when it is compared to that of the control group. Furthermore, the hypoxia treatment group had a higher content of MDA compared to that of the control group. Conclusion: Acute hypobaric hypoxia promotes oxidative stress which can cause serious damage to the brain tissues.